Characterisation and influence of cerium and chromium on the photocatalytic activity of sol-gel derived titanium dioxide under sunlight radiation / Siti Zulaikha Suhaili - Suhaili, Siti Zulaikha (2016)
Semiconductor titanium dioxide is a promising photocatalyst however due its wide band gap only ultraviolet region can be utilized for waste water treatment application. Therefore, in this thesis focuses on the preparation and characterization of pure titanium dioxide, cerium doped titanium dioxide and chromium doped titanium dioxide at doping levels ranging from 0.1 to 1.0 wt%. The primary objective of this study is to narrow the TiO2 band gap energies in order to enhance the photocatalytic efficiency under visible light. Samples was synthesized via sol-gel method and characterized by X-Ray diffraction method (XRD), Field Emission Scanning Electron Microscope (FESEM) and also UV-Vis diffused reflectance spectroscopy (DRS). The photocatalytic activity under visible sunlight illumination was demonstrated by photocatalytic decomposition of methylene blue in water using UV/Vis spectrophotometer. XRD pattern of samples heated at 500oC for 4 hours revealed that pure titanium dioxide consists of both polymorphs anatase and rutile. Cerium doping appeared to have inhibited the anatase-rutile phase transformation while Chromium doping resulted in a lower anatase to rutile phase transformation (A-R transformation) at highest Chromium doping. The morphology on doped samples showed conjugated spherical particles. The diffuse reflectance analysis demonstrated that the absorption edge cerium and chromium dopants helped to reduce the band gap energy by shifting towards the visible region. The photocatalytic activity of doped titanium dioxide with lower band gap energy presented higher percentage of methylene blue degradation compared to pure titanium dioxide. However, cerium doping gave better photocatalytic performance compared to chromium doping with energy band gap is 2.79 eV and 89% of degradation methylene blue. Meanwhile, the simple models of cerium and chromium doped titanium dioxide were built to study the influence of both dopants on TiO2 and the corresponding electronic structures were calculated and consistent with theoretical results by the Density Functional Theory (DFT) method. It can be concluded Ce-doped TiO2 is a suitable photocatalyst under visible light.